Analisis Pengumbaran Privasi Artis pada Tayangan Program “Insert Pagi” Trans TV Tanggal 1 Desember 2024: (Kajian dari Sudut Pandang Pedoman Perilaku Penyiaran dan Standar Program Siaran) P3SPS - Syahlun Fikry Riyanto; Fal Harmonis (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
For decades, television as a mass media has been the most popular medium for entertainment and information. Because of its audiovisual nature, television can present music shows, movies, soap operas, variety shows, reality shows, and other programs involving celebrities adored by the public. The purpose of this study is to understand and analyze the exposure of artists' privacy on the Insert Pagi program on TRANS TV on December 1, 2024, from the perspective of the Broadcasting Behavior Guidelines for Standard Broadcasting Programs (P3SPS). Several related theories are involved in this research, including TV Production, Broadcasting, Television, Television Program Genres, Infotainment, Broadcasting Law and Ethics, and the Broadcasting Behavior Guidelines for Standard Broadcasting Programs (P3SPS). The method used in this study is descriptive qualitative. The data collection techniques conducted by the researcher include in-depth interviews, documentation, and observation. The result of this research on the Insert Pagi program on December 1, 2024, is the discrepancy of the program that was broadcast due to the information presented not aligning with the provisions of the articles of P3SPS. This is evident in the exposure of the privacy of artist couple Andrew Andika and Tengku Dewi in the broadcast. As stated in the Broadcasting Behavior Guidelines Article 13, which reads, “Broadcasting institutions must respect a person’s privacy rights in producing and/or broadcasting a program, whether live or recorded.